THE PROCESS OF NATIONAL GROWTH IN SOCIETY AND ITS HARMONY WITH SOCIO-POLITICAL REFORMS - Alisher Qurbon o’g’li Ibragimov (Scholar Express Journals, 2022)
This article describes the conditions of national development in our country, its progress, the history and implementation of reforms in the social sphere, the provision of human interests, its importance in the development of the country and society, the principles of national development, the value of man and his vitality.
Keywords: National growth; human; democracy; civil society